(untitled) (Development Service Industry Management, 2023)
The article examines the popularization of oriental cuisine in restaurants. It is noted that oriental cuisine has many features that distinguish it from European cuisine. It was determined that there is cultural exchange in Ukraine, interest in lifestyle and gradual saturation of the Ukrainian market with products from the East. All this forms the demand for oriental cuisine in Ukraine, as well as gives opportunities to create restaurants with oriental dishes. In recent years, a trend of multiculturalism has been created in Ukraine. This is a characteristic of the cooking of oriental cuisine, which has its own philosophy, that is, they adhere to the so-called dogma - absolutely every dish, whether it is an appetizer or a dessert, must have all four main taste characteristics: saltiness, sweetness, sourness and spiciness. The number of restaurants with certain types of oriental cuisine in Ukraine by city was analyzed. The most popular restaurant establishments with oriental cuisine in Ukraine are developed in such cities as: Kyiv, Odesa, Dnipro, Kharkiv and Lviv. It is noted that sushi delivery from restaurants is also in demand in Ukraine. Also, the number of companies that have their own delivery service or work in the format of online sushi bars, online restaurants of oriental cuisine is increasing. It is noted that the most popular ingredient of oriental dishes remains shrimp. It was determined that in restaurants with oriental cuisine, great attention is paid to the design and serving of dishes, because this is the tradition and culture of eating oriental cuisine. It has been proven that restaurant establishments with oriental cuisine act as guides of national culinary art, national cuisine, national traditions of food preparation and consumption, therefore the role of the restaurant industry in the processes of interpenetration of national cultures is very large. It was concluded that quite often restaurant establishments do not dare to take risks and adapt recipes and methods of food preparation to the tastes familiar to our people. But oriental cuisine is an opportunity to experiment with flavors and enjoy the most unusual combinations of products, opening up an unusual world of traditions and exoticism.